PERBEDAAN STRUKTUR XILEM BATANG SENGON (Falcataria moluccana) DARI PROVENAN SOLOMON DAN WAMENA - Lucy Ana Cahya Inkasari; Liliana Baskorowati; Anti Damayanti (Jurnal Pemuliaan Tanaman Hutan, 2016)
Sengon (Falcataria moluccana) is fast growing species mostly planted by farmers due to its high productivity. Sengon originating from Solomon Island has been known with the high productivity eventhough susceptible to gall rust attack; on the other hand, sengon originating from Wamena is known to be more tolerant to gall rust attack. There is no previous study in terms of stem xylem structures comparing sengon from those seed origins. Therefore, this study was undertaken to identify the differences in anatomical structure of sengon stem; and to compare the xylem cell based on proportions and dimensions of the stems between the two provenances. Six stem samples of tolerant Wamena provenance and six samples of susceptible Solomon provenance were used in this study. Samples were collected from progeny trial of sengon in Lumajang, Jawa Timur. The observations include the anatomical structures and vessel element, parenchyma apotracheal cell, parenchyma paratracheal cell, xylem fiber, fiber length, and fiber diameter. The result showed that there was no difference in terms of anatomical structures between sengon Wamena (tolerant) and Solomon (susceptible) stem in cross section, tangential and radial section of periderm, phloem, secondary xylem (vessel cell, xylem fiber, and parenchyma xylem) and pith. However, in one of susceptible stem sample, a black reaction zone on the secondary xylem was found. Analysis of variance showed that parenchyma paratracheal cell, apotracheal cell, number of xylem fibers, xylem fiber diameter and length were not significantly different between stem of sengon Wamena (tolerant) and Solomon (susceptible).